2013
DOI: 10.1016/j.bbadis.2013.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar ATPase driven potassium transport in highly metastatic breast cancer cells

Abstract: Breast cancer is the second leading cause of death in women and thus has received a great deal of attention by researchers. Recent studies suggested decreased occurrence of cancer in patients treated with cardiac glycosides (CGs) for heart conditions. Because CGs induce their cellular effects via the Na(+), K(+) ATPase (Na-K), we treated four breast cancer cell lines (MCF-7, T47D, MDA-MB453, and MDA-MB231) and a non-cancerous breast ductal epithelial cell line (MCF-10A) with ouabain, a well-characterized CG, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…36,37,45 More studies to investigate the mechanistic anticancer effect of GaNPs are required Cancer cells exhibit fundamentally different metabolic pathways for maintenance of intracellular ion homeostasis concerning Na+/K+-ATPase activity markedly depends on tumor cell or cancer type. 58 In this regard, the obtained data showed a significant decrease of Na+/K+-ATPase activity in cancerbearing mice (EC group) in comparison with other treated groups (EC+R and EC+GaNPs+R). This finding is consistent with others 59,60 who reported that hepatic Na+/K+-ATPase activity concentration was significantly decreased in tumor-bearing mice when compared to control.…”
Section: Discussionmentioning
confidence: 73%
“…36,37,45 More studies to investigate the mechanistic anticancer effect of GaNPs are required Cancer cells exhibit fundamentally different metabolic pathways for maintenance of intracellular ion homeostasis concerning Na+/K+-ATPase activity markedly depends on tumor cell or cancer type. 58 In this regard, the obtained data showed a significant decrease of Na+/K+-ATPase activity in cancerbearing mice (EC group) in comparison with other treated groups (EC+R and EC+GaNPs+R). This finding is consistent with others 59,60 who reported that hepatic Na+/K+-ATPase activity concentration was significantly decreased in tumor-bearing mice when compared to control.…”
Section: Discussionmentioning
confidence: 73%
“…For example, in many breast cancer cell lines, there is an upregulation in the expression of V-ATPases in the cell membrane whereas overexpression in normal cells confers a neoplastic phenotype [85, 86]. Another voltage-gated proton pump Hv1, critical for proton transfer, is overexpressed in high-grade metastatic human breast cancer cell lines such as MCF-7, but shows minimal expression in low-grade metastatic breast tumors [87].…”
Section: 0 Tmp and Cancermentioning
confidence: 99%
“…The monoclonal NKA β 1 antibody (#MA3-930) has been used previously in this journal to quantify β 1 protein in human muscle samples despite no clear evaluation of specificity of the lot used (Murphy et al , 2004). As β 1 protein is heavily glycosylated (Vagin et al , 2006), and highly expressed in human cancer cell lines (Salyer et al , 2013), we tested the specificity of our β 1 antibody lot using deglycosylated (PNGase treated for 3 h) and control human crude skeletal muscle samples and two human breast cancer (MDA-MB-231 and MCF10.Ca1d) and control (HEKs, human embryonic kidney) cell lines (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%